The seven wonders of Sassafras Springs - Birney, Betty G.; Phelan, Matt (New York : Aladdin Paperbacks, 2007)
Eben McAllister searches his small town to see if he can find anything comparable to the real Seven Wonders of the World.
4.8
3-6
3-6
Wilson's Children
School Library Journal
Book Links (A.L.A.)
Keywords: Curiosities and wonders -- Juvenile fiction; Country life -- Juvenile fiction; Families -- Juvenile fiction; Neighbors -- Juvenile fiction; Curiosities and wonders -- Fiction; Country life -- Fiction; Family life -- Fiction; Neighbors -- Fiction; Curiosities and wonders -- Fiction; Country life -- Fiction; Family life -- Fiction; Neighbors -- Fiction